Pengaruh Pemberian Senam Aerobic Intensitas Sedang Dan Tinggi Terhadap Penurunan Berat Badan - Nastiti, Iradian; , Dwi Rosella K, S.St FT., M.Fis; , Dwi Kurniawati, SSt.FT (2016)
Background:Overweight is a medical condition such as excess body fat that accumulates in a way that adversely affect health. Overweight is a problem that is experienced by various circles, especially in adult women. Eating fast food with high calories, less exercise and are accustomed to living leisurely make weight gain more and more uncontrollable. To overcome the problem of excess weight one can do aerobics. Objective: To determine the effect of different aerobic exercise of moderate intensity and height to weight loss. Methods: Quasi-Experimental Research uses methods to design research Pre and Post Two Group Design by comparing the two treatments, ie, moderate-intensity aerobic exercise and high intensity aerobic exercise performed for 4 weeks with 10 respondents. Data analysis techniques in this study to test the effect of using Wilcoxon and Mann Whitney test for different test influence. Result: the effect of moderate intensity aerobic exercise and high for weight loss using the Wilcoxon test that moderate-intensity aerobic exercise with the results mean p = 0.034 p <0.05 can be concluded no significant effect on weight loss and high intensity aerobic exercise the results mean p = 0.038 p <0.05 it can be concluded there is a significant impact on weight loss. To test the difference between the 2 treatment effect using the Mann Whitney test results mean p = 0.006 p <0.05 it can be concluded there is a significant difference between moderate-intensity aerobic exercise san height to weight loss. Conclusions: There is a significant difference between aerobic exercise of moderate intensity and height to weight loss. Keywords: Aerobic Gymnastics, Aerobics Intensity Medium, High Intensity Aerobic, Weight